The Effect of Social Media on Purchasing Decisions Through Consumer Motivation on Thevioletas Fast Fashion Muslim Clothing Products - Sylva Maharani Fahira; Dela Resita Dewi; Lis Tatin Hernidatiatin (Indonesian Journal of Business Analytics, 2025)
This study examines how social media affects consumer motivation and buy decisions for fast fashion Muslim garment business Thevioletas. A quantitative and survey method was utilised to collect data from 111 social media users via an online questionnaire. Social media strongly influences consumer motivation and buying decisions, as shown by a R Square value of 0.843. Validity and reliability assessments confirmed the study instruments' correctness and consistency with a Cronbach's Alpha of 0.928. Consumer motivation indirectly influences social media and purchasing decisions, even if it does not directly effect social media engagement. These findings underline the importance of effective digital marketing and a full understanding of motivational factors like trends, self-identity, comfort, and religious beliefs to boost Muslim fashion product purchases.